Mitochondrial alterations triggered by repeated exposure to fine (PM2.5-0.18) and quasi-ultrafine (PM0.18) fractions of ambient particulate matter. (September 2020) - Sotty, J.; Kluza, J.; De Sousa, C.; Tardivel, M.; Anthérieu, S.; Alleman, L.-Y.; Canivet, L.; Perdrix, E.; Loyens, A.; Marchetti, P.; Lo Guidice, J.-M.; Garçon, G.
Graphical abstract: Highlights: Better knowledge of the critical role of mitochondrion in FP and Q-UFP-induced lung toxicity. Mitochondrial ROS overproduction and activation of NRF2-ARE signaling pathways. Mitochondrial dynamics modifications in favor of accentuated fission process. Mitochondrial quality control and metabolism dysfunctions as underlying mechanism of toxicity. New insights into the physiopathology-induced by FP and mostly Q-UFP within the lung. Abstract: Nowadays ambient particulate matter (PM) levels still regularly exceed the guideline values established by World Health Organization in most urban areas. Numerous experimental studies have already demonstrated the airway toxicity of the fine fraction of PM (FP), mainly triggered by oxidative stress-induced airway inflammation. However, only few studies have actually paid close attention to the ultrafine fraction of PM (UFP), which is likely to be more easily internalized in cells and more biologically reactive. Mitochondria are major endogenous sources of reactive oxygen species (ROS) through oxidative metabolism, and coordinate many critical cellular signaling processes. Mitochondria have been often studied in the context of PM toxicity and generally associated with apoptosis activation. However, little is known about the underlying adaptation mechanisms that could occur following exposure at sub-apoptotic doses of ambient PM. Here, normal human bronchial epithelial BEAS-2B cells were acutely or repeatedly exposed to relatively low doses (5 µg.cm −2 ) of FP (PM2.5-0.18 ) or quasi-UFP (Q-UFP; PM0.18 ) to better access the critical changes in mitochondrial morphology, functions, and dynamics. No significant cytotoxicity nor increase of apoptotic events were reported for any exposure. Mitochondrial membrane potential (ΔΨm) and intracellular ATP content were also not significantly impaired. After cell exposure to sub-apoptotic doses of FP and notably Q-UFP, oxidative phosphorylation was increased as well as mitochondrial mass, resulting in increased production of mitochondrial superoxide anion. Given this oxidative boost, the NRF2-ARE signaling pathway was significantly activated. However, mitochondrial dynamic alterations in favor of accentuated fission process were observed, in particular after Q-UFP vs FP, and repeated vs acute exposure. Taken together, these results supported mitochondrial quality control and metabolism dysfunction as an early lung underlying mechanism of toxicity, thereby leading to accumulation of defective mitochondria and enhanced endogenous ROS generation. Therefore, these features might play a key role in maintaining PM-induced oxidative stress and inflammation within lung cells, which could dramatically contribute to the exacerbation of inflammatory chronic lung diseases. The prospective findings of this work could also offer new insights into the physiopathology of lung toxicity, arguably initiate and/or exacerbate by acutely and rather repeated exposure to ambient FP and mostly Q-UFP.